2019
DOI: 10.21315/mjms2019.26.5.12
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative Sore Throat: Comparing the Monitored Endotracheal Tube Cuff Pressure and Pilot Balloon Palpation Methods

Abstract: BackgroundEndotracheal tube cuff (ETTc) inflation pressure is usually not regarded as an important aspect during intubation. In this study, we compared measuring ETTc pressure and pilot balloon palpation method in causing post-operative airway complications.MethodsTwo hundred and ninety-two surgical patients requiring intubation were recruited into this prospective, double-blind, randomised controlled study. Group A patients had their ETTc initially inflated, checked by a cuff pressure gauge, recorded and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 14 publications
0
11
0
4
Order By: Relevance
“…It was so unreliable that its use in Iranian ICU patients was associated with universal over-inflation of the tracheal cuff, with all being above 40 cmH 2 O (mean 88.8 ± 27.1 cmH 2 O) [ 25 ]. The use of tracheal cuff manometer for objective estimation and monitoring of tracheal cuff pressure reduces postoperative morbidity [ 1 , 26 ]. The very limited use of the manometer in tracheal cuff management in the country cannot be explained away by mere unavailability since other devices for monitoring patients such as the multi-parameter patient monitors are available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was so unreliable that its use in Iranian ICU patients was associated with universal over-inflation of the tracheal cuff, with all being above 40 cmH 2 O (mean 88.8 ± 27.1 cmH 2 O) [ 25 ]. The use of tracheal cuff manometer for objective estimation and monitoring of tracheal cuff pressure reduces postoperative morbidity [ 1 , 26 ]. The very limited use of the manometer in tracheal cuff management in the country cannot be explained away by mere unavailability since other devices for monitoring patients such as the multi-parameter patient monitors are available.…”
Section: Discussionmentioning
confidence: 99%
“…The cuff also facilitates positive pressure ventilation by forming a good seal with the tracheal mucosa thereby preventing leakage of fresh gas. Over‐inflation of tracheal tube cuff has been associated with postoperative sore throat [ 1 ], tracheal oesophageal fistula [ 2 , 3 ], and tracheal stenosis [ 4 ]. Conversely under-inflation of the tracheal cuff has been implicated with ventilator-associated pneumonia (VAP) [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Endotrakealtuber og larynxmasker blir benyttet ved anestesi og utstyrt med en ballong/ cuff for å tette mellomrommet mellom tube/maske og luftrøret. Studier viser at pasienter i generell anestesi som har fått sine luftveier sikret med endotrakealtube har skader i slimhinner eller opplever hoste, sår hals, heshet eller problemer med å svelge postoperativt (1)(2)(3). De samme skader rapporteres også ved bruk av larynxmasker (4)(5)(6).…”
Section: Bakgrunnunclassified
“…Over halvparten (60 %) av cufftrykkene i endotrakealtubene var utenfor de anbefalte grensene, og 25 % var over okklusjonsgrensen på 50 cmH 2 O med økt risiko for alvorlige komplikasjoner i luftveiene. Dette samsvarer med andre studier som er blitt gjort på cufftrykk i endotrakealtuber (1)(2)(3).…”
Section: Diskusjonunclassified
“…Although ETT cuff pressure management techniques include the predetermined volume technique, palpation technique, syringe technique, and minimal occlusive volume technique, the gauge manometer is the most reliable manual measurement and is widely recommended 5,6,19 (Siamdous et al, 2015AQ4). However, a gauge manometer is not routinely used in actual practice in some ICUs, 19 and previous studies highlighted that the subjective practice of estimation using finger palpation still exists among practitioners, for example, in Pakistan, 14 Sri Lanka, 5 Egypt (Khalil et al, 2018), Malaysia, 20 Italy, 21,22 India, 23 South Africa, 24 and the United States, 6 among others. An observational cross‐sectional study in Melbourne, Australia, which assessed the minimal leak test and cuff manometer techniques, noted that the minimal leak test results in a cuff pressure outside the recommended range; thus, the authors suggested the use of the cuff manometer technique for reliable practice 25 …”
Section: Introductionmentioning
confidence: 99%